An evaluation study on immigrants′ transport system adaptation behaviour: Turkey example - Aydin, Metin Mutlu; Dağli, Eren; Çadirci, Mehmet Sıddık (Transport, 2025)
Global migration patterns have led to significant population shifts, particularly in regions such as Turkey, which has experienced a substantial influx of immigrants due to political crises, economic instability, and armed conflicts. This study examines the adaptation behaviour of immigrants to Turkey′s transport system, identifying key challenges, expectations, and integration patterns. Using survey data from immigrants in Turkey, the study explores the role of demographic factors, prior transport experiences, and socio-economic conditions in shaping mobility choices. The findings indicate that while many aspects of Turkey′s transport system are familiar to immigrants, significant barriers such as high travel costs, unclear traffic signage, and language-related difficulties hinder complete adaptation. Younger, higher-educated immigrants and those from culturally similar backgrounds demonstrate a faster integration process, whereas older immigrants and those with limited educational backgrounds face more significant obstacles. Statistical analyses, including multiple linear regression and decision tree classifier, reveal that age is the most significant predictor of long-term transport adaptation. Additionally, the study highlights that as the duration of stay increases, immigrants exhibit a higher reliance on public transportation, with ownership of private vehicles gradually rising among long-term residents. The research underscores the need for policy interventions, such as reducing transport costs, improving multilingual signage, and offering integration programs to enhance immigrant mobility. These insights provide valuable guidance for policymakers, urban planners, and transport authorities striving to develop more inclusive and efficient transport systems.